2020
DOI: 10.1111/psyg.12523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a practical training programme on burnout among professional caregivers in a care home for older adults with dementia: a pilot study

Abstract: Aim As the number of persons with dementia has increased so has the need for both specialized care and long‐term care centres. Professional caregivers working in these centres encounter specific problems, including stress, burnout, and feelings of dissatisfaction, each which can affect the quality of care. Due to the nature of their work, they are more likely to experience stress, which may lead to burnout syndrome. Therefore, the aim of this work was to assess the results of a practical training programme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
3
Order By: Relevance
“…There was a smaller set of papers (9) which linked recommendations to evidence of improved psychosocial support for care workers. This included demonstrating reduction in burn‐out through dementia care training 56 and improved sense of well‐being through the use of ‘creative breaks’ 57…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a smaller set of papers (9) which linked recommendations to evidence of improved psychosocial support for care workers. This included demonstrating reduction in burn‐out through dementia care training 56 and improved sense of well‐being through the use of ‘creative breaks’ 57…”
Section: Resultsmentioning
confidence: 99%
“…55 There was a smaller set of papers ( 9) which linked recommendations to evidence of improved psychosocial support for care workers. This included demonstrating reduction in burn-out through dementia care training 56 and improved sense of well-being through the use of 'creative breaks'. 57 Looking at the two studies within the 'revitalise' theme, Neal 58 reported on an initiative using university students from the United States of America to deliver some social care services in Nicaragua.…”
Section: Direct Evidencementioning
confidence: 99%
“…A range of NPT are available, such as socio and psycho-educational approaches, cognitive and emotion interventions, physical exercise and sensorial activities (e.g., music, art and massage therapies). Other psychoeducational interventions are linked to training professionals and informal caregivers in order to reduce their stress/burnout and to improve their knowledge on dementia care ( Barbosa et al, 2014 ; Briones-Peralta et al, 2020 ). Among all, music interventions targeted to older people with dementia seem to be the most effective NPT to manage BPSD ( Abraha et al, 2017 ; Dyer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…State of mind plays a major role in work productivity and efficiency. Burnout has been described as a consequence of severe stress in the workplace that affects one’s physical and psychological performance [ 1 , 2 ]. Burnout begins when a person feels overstressed in the workplace due to lack of control, work-life imbalance, and a dysfunctional workplace [ 3 ].…”
Section: Introductionmentioning
confidence: 99%